Modulation of Immune Responses by Nutritional Ligands of Aryl Hydrocarbon Receptor - De Juan, Alba; Segura, Elodie (Frontiers in Immunology, 2021)
Accumulating evidence indicates that nutrition can modulate the immune system through metabolites, either produced by host digestion or by microbiota metabolism. In this review, we focus on dietary metabolites that are agonists of the Aryl hydrocarbon Receptor (AhR). AhR is a ligand-activated transcription factor, initially characterized for its interaction with xenobiotic pollutants. Numerous studies have shown that AhR also recognizes indoles and tryptophan catabolites originating from dietary compounds and commensal bacteria. Here, we review recent work employing diet manipulation to address the impact of nutritional AhR agonists on immune responses, both locally in the intestine and at distant sites. In particular, we examine the physiological role of these metabolites in immune cell development and functions (including T lymphocytes, innate-like lymphoid cells, and mononuclear phagocytes) and their effect in inflammatory disorders.